Formulation and evaluation of immediate release tablet of zopiclone using wet granulation method - Bhatt, Rajesh; Sharma, Aditya; Kumar, Prevesh; Upadhyay, Sukirti; Upadhyay, Prashant (Journal of Drug Delivery and Therapeutics, 2019)
Zopiclone, a cyclopyrolone, is a non-benzodiazepine derivative used as a hypnotic agent in the treatment of short term insomnia. The main objective of the present investigation was to formulate a pharmaceutically active stable and bioequivalent immediate release (IR) tablets of zopiclone using wet granulation method. The prepared formulations were evaluated using various physical parameters, equipment, dissolution study and drug release profile.  The basic approach used in development of zopiclone IR tablets was that the use of superdisintegrants as like Corn starch (maize) and Sodium starch glycolate which provide instant disintegration after administration. In-vitro dissolution testing study was carried out for 1 hours using 0.1N HCl in a dissolution apparatus for evaluation of Drug release. On the basis of the dissolution profile, F3 gives a better result and were found 100 % release in just 20 minutes and also found that as the polymer ratio were increases the drug release rate also increased from the formulation.Keywords: Hypnotic agent, immediate release, Wet granulation Method, Non-benzodiazepine derivative, Superdisintegrants, Zopiclone